READING LEARNING BASED ON LOCAL WISDOM - Nila kencana; Elva Utami; Yuneva Syukur (STKIP Siliwangi, 2024)
The study explores local value/wisdom and the cultural views of Bengkulu people, which is dealing with the teaching materials for reading skill. This study aims to develop reading materials in the basis of on local value that are effective, valid, and practical for English major students. This is a research and development (RnD) using ADDIE model applied to the Students of the English Language Study Program Semester IV, Universitas Prof. Dr. Hazairin, SH Bengkulu. The results of the study show that the teaching materials for reading skill based on the local wisdom has been developed is valid, practical and effective. It is based on the expert’s and validator’s evaluation and proved that the learning outcomes reaching 92.5% of all learning outcomes are valid and feasible. The practicability of the product showed based on the students’ responses which is gained the achievement of student activities reached ≥ 75% of the 5 observed activity indicators, while the average response of all students reached 80%. It indicates that students responded positively reaching ≥ 75%.